Adoptive Transfer of Allogeneic Liver Sinusoidal Endothelial Cells Specifically Inhibits T-Cell Responses to Cognate Stimuli. Issue 9 (September 2013) - Banshodani, Masataka; Onoe, Takashi; Shishida, Masayuki; Tahara, Hiroyuki; Hashimoto, Shinji; Igarashi, Yuka; Tanaka, Yuka; Ohdan, Hideki
Although it is well known that liver allografts are often accepted by recipients, leading to donor-specific tolerance of further organ transplants, the underlying mechanisms remain unclear. We had previously used an in vitro model and showed that mouse liver sinusoidal endothelial cells (LSECs) selectively suppress allospecific T-cells across major histocompatibility complex (MHC) barriers. In the present study, we established an in vivo model for evaluating the immunomodulatory effects of allogeneic LSECs on corresponding T-cells. Allogeneic BALB/cA LSECs were injected intraportally into recombination activating gene 2 γ-chain double-knockout (RAG2/gc-KO, H-2 b ) mice lacking T, B, and natural killer (NK) cells. In order to facilitate LSEC engraftment, the RAG2/gc-KO mice were injected intraperitoneally with monocrotaline 2 days before the adoptive transfer of LSECs; this impaired the host LSECs, conferring a proliferative advantage to the transplanted LSECs. After orthotopic allogeneic LSEC engraftment, the RAG2/gc-KO mice were immune reconstituted intravenously with C57BL/6 splenocytes. After immune reconstitution, mixed lymphocyte reaction (MLR) assay using splenocytes from the recipients revealed that specific inhibition of host CD4 + and CD8 + T-cell proliferation was greater in response to allostimulation with irradiated BALB/cA splenocytes rather than to stimulation with irradiated third party SJL/jorllco splenocytes. This inhibitory effect was attenuated by administering anti-programmed death ligand 1 (PD-L1) monoclonal antibody during immune reconstitution in the above-mentioned mice, but not in RAG2/gc-KO mice engrafted with Fas ligand (FasL)-deficient BALB/cA LSECs. Furthermore, engraftment of allogeneic BALB/cA LSECs significantly prolonged the survival of subsequently grafted cognate allogeneic BALB/cA hearts in RAG2/gc-KO mice immune reconstituted with bone marrow transplantation from C57BL/6 mice. In conclusion, murine LSECs have been proven capable of suppressing T-cells with cognate specificity for LSECs in an in vivo model. The programmed death 1/PD-L1 pathway is likely involved in these suppressive effects.